Entrepreneurial Capital and Firm Performance: Gendered Experiences in North and South Europe - Díaz-García, María Cristina; Shaw, Eleanor; Carter, Sara (Senate Hall, 2009)
This paper explores the relationship between gender, entrepreneurial capital and firm performance. Two comparable surveys (Scotland, Spain), each comprising thirty matched pairs of business owners (30 male, 30 female) drawn from the professional business services sector provide four distinctive groups of entrepreneurs (female Spanish, male-Spanish, female-Scottish, male-Scottish). The study views entrepreneurship as being socially embedded, hence owners' constructions of their social realities in the context of business ownership were included in the analysis. The results show significant differences in the amounts of human, social and financial capital used by the four groups of entrepreneurs and in the subsequent performance of their ventures. Variations by gender and by region are discussed in relation to theories of entrepreneurial capital. Keywords: gender, entrepreneurial capital, firm performance, context.
Keywords: gender|entrepreneurial capital|firm performance|context